KAJIAN AKTIVITAS BIOAKTIF EKSTRAK TERIPANG PASIR (Holothuria scabra) TERHADAP JAMUR Candida albicans - Pranoto, Eunike Noviana; Ma'ruf, Widodo Farid; Pringgenies, Delianis (Jurusan Perikanan, Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
Sea cucumbers are found in Indonesian oceans. Sea cucumbers have been known containing substances as antifungal. Infection diseases in human caused by fungi, such as Candida albicans, are still high and antifungal drugs are less than antibacterial drugs in amount. Medical curing of Candidiasis chemically can use chemical agents. But they can caused resistance and side effects. The purpose of this research is to know the influence of different solvent and concentration usage of Holothuria scabra extract towards C. albicans and to know the bioactive substances contained in H. scabra. The results obtained from this research were: the best solvent to extract antifungal agents from H. scabra is methanol. Extract concentration of 5 mg/ml, 6 mg/ml,7 mg/ml showed inhibition zone continuously as high as 5,1 + 0,56 mm; 8,42 + 0,71 mm; 10,1 + 0,59 mm. The results are significantly different (P < 0,01), different (0,01 < P < 0,05), and not different (P > 0,05) for antifungal activity test. Bioactive substance test showed that alkaloid, saponin, steroid, and triterpene were found in H. scabra. H. scabra extract indicates potential activity as antifungal agent. Â Â